A corpus-informed study of discourse connectives in narrative essays of secondary school students / Siti Syairah Fakhruddin - Siti Syairah , Fakhruddin (2018)
The use of English language has been steadily increasing as more people can be seen to use the language in their everyday conversations. English users who express the language in written form have to include discourse connectives in their texts. Discourse connectives are important indicators of textual coherence and have the purpose of unifying a text. Previous studies have investigated the types of discourse connectives used in L2 learners’ texts (Granger & Tyson, 1996; Hinkle, 2003; Hamed, 2014). However, students’ views regarding their own use of discourse connectives were often not considered in those studies. In this corpus-informed study, the semantic use of discourse connectives in a corpus of 96 narrative essays written by 32 students and interviews with 10 selected students regarding their views on their own use of discourse connectives were explored. Drawing on this corpus of learners’ written texts, this study adapted the frameworks by Halliday and Hasan (1976) and Hyland (2005) in order to categorise the discourse connectives used in learners’ texts. Analysis of the corpus revealed that additive discourse connective was the most frequently used type of discourse connectives, while and, but, because, so and then occurred as the top five most frequently used discourse connectives in the students’ written texts. This study also uncovered the students’ own preferred discoursal practices. For instance, some of them used more DCs in their texts while others used less DCs in their texts. Moreover, the findings from this study indicated that some students tend to use different types of discourse connectives in their sentences although they were aware that there were other types of discourse connectives that could be used. There were also some students who used some DCs not in accordance with the related frameworks which shows their innovative ways of using the DCs. Most importantly, the findings from this study reveal that it is time to appreciate L2 learners’ choices for using discourse connectives in their texts. In conclusion, it is hoped that the findings in this study will bring awareness to linguists that the most important thing for L2 learners is to become accomplished users of English and not imitations of native speakers (Larsen-Freeman, 2011; Cook, 2013).